2016
DOI: 10.1007/s10103-016-2051-3
|View full text |Cite
|
Sign up to set email alerts
|

Peri-implant osseointegration after low-level laser therapy: micro-computed tomography and resonance frequency analysis in an animal model

Abstract: The purpose of the present study is to evaluate the effects of low-level laser therapy on the osseointegration process by comparing resonance frequency analysis measurements performed at implant placement and after 30 days and micro-computed tomography images in irradiated vs nonirradiated rabbits. Fourteen male New Zealand rabbits were randomly divided into two groups of seven animals each, one control group (nonirradiated animals) and one experimental group that received low-level laser therapy (Thera Lase®,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…The animal studies have all reported that photo therapy with low levels of light can provide greater bone-implant interface strength and also improve the osseointegration process (Table 2). 6,15,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] Removal torque values increased significantly along with time even after a single laser irradiation compared with a nonirradiated control group in the study by Boldrini et al 24 Gomes et al have interestingly shown that higher energy levels (10 or 20 J/cm 2 ) promote more implant-bone contact compared with a lower energy (5 J/cm 2 ). Better ISQ values were also observed in the 20 J/cm 2 group (this article was published in the Quintessense journal in the same year with the Mayer et al bibliography).…”
Section: Can Photobiomodulation Influence Ti Implant Stability?mentioning
confidence: 99%
See 1 more Smart Citation
“…The animal studies have all reported that photo therapy with low levels of light can provide greater bone-implant interface strength and also improve the osseointegration process (Table 2). 6,15,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] Removal torque values increased significantly along with time even after a single laser irradiation compared with a nonirradiated control group in the study by Boldrini et al 24 Gomes et al have interestingly shown that higher energy levels (10 or 20 J/cm 2 ) promote more implant-bone contact compared with a lower energy (5 J/cm 2 ). Better ISQ values were also observed in the 20 J/cm 2 group (this article was published in the Quintessense journal in the same year with the Mayer et al bibliography).…”
Section: Can Photobiomodulation Influence Ti Implant Stability?mentioning
confidence: 99%
“…Most of these studies reported positive effects in terms of promotion of bone formation around Ti implants, and higher bone implant contacts (BICs) were reported ( Table 1). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Many researchers have confirmed that low-level light therapy can promote bone formation by stimulatory effects on osteoblasts, which can lead to greater osteo-integration of Ti implants. This has been evaluated in different study designs and laser irradiation parameters.…”
mentioning
confidence: 99%
“…The RFA has been successfully used in clinical studies as the only non-invasive, functional measurement method. It is regarded as a sufficient tool for evaluating the course of intraosseous implant stability in clinical practice [9,[51][52][53] and in preclinical settings [54][55][56][57][58]. We found that ISQ values moderately changed with healing time.…”
Section: Discussionmentioning
confidence: 72%
“…Some of the studies did not detect any change during healing between primary and secondary stabilities with RFA [59,60]. In contrast, other results showed a dynamic increase in ISQ values from primary to secondary stability [9,[54][55][56][57][58]. Taken together, RFA is an appropriate method for determining differences between very early and late stages of osseointegration.…”
Section: Discussionmentioning
confidence: 95%
“…30 In the last decades, the use of LLLT has been widely studied in dentistry. [31][32][33][34] In oral implantology, some studies have assessed the use of LLLT to improve the primary stability at the early stages of osseointegration [7][8][9] ; however, most of these studies were performed in animal models. As stated earlier, the last systematic review on this topic suggested that there is a lack of evidence about the influence of LLLT on implant stability in humans.…”
Section: Discussionmentioning
confidence: 99%